Cardiovascular device infections due to rapidly growing Mycobacteria: A review of cases at a tertiary care hospital. (February 2022) - Comba, Isin Yagmur; Chesdachai, Supavit; Tabaja, Hussam; Mahmood, Maryam; Deml, Sharon; Wengenack, Nancy L.; Wilson, John W.
Abstract: Cardiovascular device infection due to rapidly growing mycobacteria (RGM) is rarely encountered in clinical practice. Due to the increasing number of indications and use of cardiovascular devices in an aging population, optimized management of these infections is of great importance. We report seven cases of RGM cardiovascular device infection. Three patients had left-ventricular assist device (LVAD) infections; two patients had cardiovascular implantable device (CIED) infections; and one had an aortic vascular stent infection. Specific cardiac valvular infection was not detected among any of the patients. All patients had a high number of comorbidities which limited some patients from receiving optimal combination antimicrobial therapy. The prognosis of cardiovascular device infections with RGM is guarded with only four patients still alive; however, the treatment approach for each patient varied considerably and often based on concurrent medical conditions, overall adjustments to goals of care, and specific patient preferences. Further analysis of cardiovascular device infections with RGM is warranted to establish a more systematic approach in successful management.